Improving Health Care Efficiency Through the Integration of a Physician Assistant into an Infectious Diseases Consult Service at a Large Urban Community Hospital - Melissa Decloe; Janine McCready; James Downey; Jeff Powis (Canadian Journal of Infectious Diseases and Medical Microbiology)
BACKGROUND: Physician assistants (PAs) have recently been introduced into the Canadian health care system in some provinces; however, there are little data demonstrating their impact.